Perceptions of prognosis and end-of-life care outcomes in patients with advanced lung and gastrointestinal cancer. (May 2023) - Gray, Tamryn F; Plotke, Rachel; Heuer, Lauren; Topping, Carlisle EW; Nipp, Ryan D; Wang, Annie C; Gasca Banda, Juan; Greer, Joseph A; Temel, Jennifer S; El-Jawahri, Areej
Background: Many patients with advanced cancer have misperceptions of their prognosis, which may impact end-of-life decision-making. Data regarding associations between prognostic perceptions over time and end-of-life care outcomes are lacking. Aim: To describe patients' perceptions of their prognosis with advanced cancer and examine associations between these perceptions and end-of-life care outcomes. Design: Secondary analysis of longitudinal data from a randomized controlled trial of a palliative care intervention for patients with newly diagnosed incurable cancer. Setting/Participants: Conducted at an outpatient cancer center in the northeastern United States and patients were within 8 weeks of a diagnosis with incurable lung or non-colorectal gastrointestinal cancer. Results: We enrolled 350 patients in the parent trial, of which 80.5% (281/350) died during the study period. Overall, 59.4% (164/276) of patients reported they were terminally ill, and 66.1% (154/233) reported that their cancer was likely curable at the assessment closest to death. Patient acknowledgment of terminal illness was only associated with lower risk of hospitalizations in the last 30 days of life (OR = 0.52, p = 0.025). Patients who reported their cancer as likely curable were less likely to utilize hospice (OR = 0.25, p = 0.002) or die at home (OR = 0.56, p = 0.043), and they were more likely to be hospitalized in the last 30 days of life (OR = 2.28, p = 0.011). Conclusions: Patients' perceptions of their prognosis are associated with important end-of-life care outcomes. Interventions are needed to enhance patients' perceptions of their prognosis and optimize their end-of-life care.